Frantz Fanon y la vía dolorosa del desarrollo de la nación argelina. - Schmidt, Axel (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
In 1956, in the midst of the Cold War, the Martinican psychologist Frantz Fanon, disappointed by the European civilization, joins the struggle of Algerian independence as its main theoretician. Having a clear vision of the goals he warns of the political obstacles in postcolonial development. However, the political future of independent Algeria depends not only on the willingness of some intellectuals but on natural conditions, historical traditions (pre-colonial, colonial and resistance) and the current international situation. Despite of very favorable initial circumstances, the country is still struggling with the challenges of the XXI century.